Effect of ethanol and methanol on the total phenolic content and antioxidant capacity of chia seeds (Salvia hispanica L.) - Morales-Olán, Gema; Rojas-López, Marlon; Díaz-Reyes, Joel; Rosas-Cárdenas, Flor de Fátima; Luna-Suárez, Silvia (Penerbit Universiti Kebangsaan Malaysia, 2020)
The use of methanol and ethanol for the extraction of antioxidant compounds in Chia Seed (Salvia hispanica L.) is studied, but only the effect of a single concentration of these solvents was evaluated. However, factors such as the nature and the concentration of the solvents determines the content of phenolic compounds, the antioxidant capacity and the possible use of the extract. For this reason, it is necessary to have a detailed study of different extraction conditions to find the optimum. The objective of this work was to evaluate the effect of different concentrations of ethanol and methanol and the hexane treatment on the extraction of phenolic compounds and the antioxidant capacity of the Chia Seeds extracts. The greatest total phenolic content was obtained in the 50% aqueous ethanol and methanol extracts. Nevertheless, all the extracts showed a high DPPH scavenging activity. With exception of 100% ethanol extract, no significant differences were found between the extracts treated with and without hexane. No significant differences were found in the extraction yields of the 80% aqueous ethanol and methanol extracts, but the aqueous methanol extract presented lower IC50. The FTIR and UV-VIS spectra of the aqueous ethanol and methanol Chia extracts suggest differences in the composition of the extracts. It is possible to extract the phenolic compounds from the Chia Seeds with different concentration of ethanol and methanol, which will allow to select the appropriate extraction conditions according to the application of the extract.